1972
DOI: 10.1177/00220345720510023501
|View full text |Cite
|
Sign up to set email alerts
|

Lased Enamel: Ultrastructural Observations of Pulsed Carbon Dioxide Laser Effects

Abstract: Scanning electron microscopic observations of the pulsed carbon dioxide laser effect on human enamel support microradiographic findings and indicate that this laser is significantly more efficient than the ruby laser within the limits of this investigation. Surface changes which were suggestive of fusion occurred between energy densities of 13 to 50 joules per square centimeter.There may be several potential applications of laser energy to dentistry. Initially, the use of the laser as a replacement for the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
11

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(98 citation statements)
references
References 7 publications
2
80
0
11
Order By: Relevance
“…Initial conventional laser ablation studies on teeth using ruby or CO 2 lasers noted significant thermal deposition leading to collateral tooth damage [16,49]. Other lasers, such as Er : YAG, reduce thermal effects considerably but cannot compete with the speed or quality of mechanical drills [50,51].…”
Section: Dental Surgerymentioning
confidence: 99%
“…Initial conventional laser ablation studies on teeth using ruby or CO 2 lasers noted significant thermal deposition leading to collateral tooth damage [16,49]. Other lasers, such as Er : YAG, reduce thermal effects considerably but cannot compete with the speed or quality of mechanical drills [50,51].…”
Section: Dental Surgerymentioning
confidence: 99%
“…Studies have been performed using different kinds of lasers, including Er:YAG lasers and Nd:YAG lasers 2) , and CO2 lasers 3,4) . Attention has focused on Er: YAG lasers due to their high efficacies in removing dental hard tissue [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the possible applications of different types of lasers in dentistry clinics, as for example, in the inhibition of carious lesions (Stern et al, 1966(Stern et al, , 1972Yamada, 1996), as well as in their removal (White et al, 1993), in the oral mucous (Taylor et al, 1965), and in gum healing (Chomette et al, 1987), among others. The scanning electron microscope has shown the different morphological alterations in the enamel and dentin surfaces irradiated with the CO 2 laser (Takahashi et al, 1998;Watanabe et al, 1986), the diode laser (Wetter, 2002), and the Nd:YAG laser (Lin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%